The effect of standard strength vs. contrast strength training on the development of sprint, agility, repeated change of direction, and jump in junior male soccer players - Hammami, M.; Negra, Y.; Shephard, R. J.; Chelly, M. S. (The Journal of Strength and Conditioning Research, 2017)
The aim was to compare the impact of 2 differing strength training (ST) programs on the athletic performance of junior male soccer players at a critical phase during their competitive season. Participants aged 16.0 ± 0.5 years were randomly assigned between control (C, n = 12), standard ST (n = 16), and contrast strength training (CST, n = 16), each performed twice a week. Athletic performance was assessed before and after the intervention using 8 tests: 40-m sprint, 4 × 5-m sprint (S4 × 5), 9-3-6-3-9 m sprint with 180° turns (S180°), 9-3-6-3-9 m sprint with backward and forward running (SBF), repeated shuttle sprint ability (RSSA), repeated change of direction (RCOD), squat jump (SJ), and countermovement jump (CMJ). The control group's (CG) performance tended to improve in some tests and decrease in others, but these changes were not statistically significant. Both training programs enhanced all sprint performances relative to controls (p = 0.05). The strength training group (SG) and the CST group (CSG) increased significantly in S180°, SBF, and S4 × 5 relative to CG, although the S4 × 5 also increased in CSG relative to SG (p = 0.05). No intergroup difference of RSSA performance was observed. The RCOD parameters increased significantly in CSG relative to both SG and CG (p = 0.05). The SJ and CMJ height increased significantly in both experimental groups (p < 0.000). We conclude that during the competitive season, some measures of athletic performance in male soccer players were increased more by 8 weeks of CST than by ST.